Prescription of physical activity in the management of high blood pressure in Australian general practices - Smith, B.; Owen, A.; Liew, D.; Kelly, D.; Reid, Christopher (Nature Publishing Group, 2019)
This study investigated the prevalence of physical activity prescriptions in the management of high blood pressure (BP), the characteristics of people given these, and whether prescriptions were associated with the physical activity beliefs and practices of patients. A retrospective cohort study was undertaken, involving 365 general practitioners (GPs) from across Australia. The records of up to 20 patients per GP with high BP (N = 6512) were audited to identify physical activity and pharmacological prescriptions over four consecutive consultations. A sub-sample (n = 535) of patients completed a physical activity questionnaire. Physical activity prescriptions were recorded for 42.6% of patients with controlled BP, 39.5% for those with mild hypertension and 35.7% of those with moderate to severe hypertension. These were more likely in patients with cardiovascular disease (OR 1.41, 95% CI 1.23–1.62) and diabetes (OR 1.21, 95% CI 1.04–1.42), and less likely in those with moderate to severe hypertension (OR 0.80, 95% CI 0.69–0.94), aged 75 years and over (OR 0.62, 95% CI 0.51–0.74) and with high cholesterol (OR 0.73, 95% CI 0.57–0.94). Patients receiving a physical activity prescription were more likely to report this behaviour as important for their health and that they had increased their levels of participation. Most patients with high BP are not receiving physical activity prescriptions, and GPs show greater readiness to address this behaviour in patients with existing chronic disease. There is a need for efficacious and practical strategies for promoting physical activity that can be adopted in the routine management of high BP in general practice.